Problematyka charakteru prawnego odpowiedzialności podmiotów zbiorowych za czyny zabronione pod groźbą kary w prawie polskim - Pniewska, Magdalena (Studia Iuridica Toruniensia, 2010)
<!--[if gte mso 9]> <![endif]--> Corporate liability for off ences was introduced to the Polish law by the Convention on the Protection of the European Communities´ Financial Interests of the 26 July 1995 and also by the First and the Second Protocol to the Convention. The Convention imposed on the Member States the obligation to apply certain measures to establish criminal liability of a person having a leading position in the legal person for the frauds against the European Communities financial interests. In the second protocol, however, there is a requirement to introduce corporate liability for such off ences committed in the corporate interest by the person who has a power of representation of the legal person, an authority to take decisions on behalf of the legal person or an authority to exercise control within the legal person. None of the mentioned acts, however, involves the provision indicating the form of corporate liability. In the Polish law there was adopted the Act of the 28 October 2002 called “The Liability of Collective Entities for Off ences”. The form of the liability established in this statute was controversial from the early beginning. There are certain points which allows to accept the idea of criminal liability of collective entities. On the other hand, there are also reasons for which it is possible to claim that corporate liability established in the Polish law is a new form of liability, only similar to criminal liability. Criminal liability of legal persons is very well known in criminal law area. Historically, the fi rst introduced model of corporate liability was so called “vicarious liability”. In the consequence, the legal person was sanctioned because a person with whom it had a bond, committed an off ence. The other form of criminal liability was “direct liability” also called “the theory of controlling off icer”. The point of the mentioned theory was to accept the acts of a person who was in the structure of corporation as the acts of the corporation itself. The third conception was the aggregation doctrine, also known as “collective knowledge” or “aggregation knowledge”. The meaning of that doctrine was an assumption that the actions taken by people who were the members of corporation , might be combined in one act of the corporation. Criminal liability of legal persons was introduced also in the Polish law by the Act of Cartel Agreements of the 13 July 1939. It is beyond a discussion that the Act of the 28 October 2002 is a piece of repressive legislation. It is strongly emphasised that criminal nature of the mentioned statue results from the Constitution. Constitutional meaning of criminal liability, however, is not the same as in Criminal Code. The another point might be the jurisprudence of the European Court of Human Rights, which accepts a wider meaning of criminal case. On the other hand, in the view of the mentioned statue, the corporation does not commit itself an act which is forbidden as an off ence but the responsibility of the corporation is a result of the act committed by its member. Thus, it is secondary liability. It is also claimed that “mens rea” and “actus reus” known in criminal law can not be attributed to corporate liability. Therefore it is justifi ed to say that there has been created a new form of liability. The similar approach seems to present the Constitutional Tribunal in the verdict of 3 November 2004, Case K 18/03. Nevertheless, some authors claim that the discussed statute has a criminal nature and it could be assessed as a pieces of Criminal Law sensu largo. Others point out that such institutions used in the statue as culpa in eliegndo or culpa in custodiendo contradict its criminal nature. It is beyond a discussion that the statute doses not refer to Criminal Code at all. Considering all above, the more convincing is the idea of “quasi-criminal liability of corporations”. That form of liability is a piece of repressive legislation. It is very similar to criminal law, but can not be counted to that branch of law. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->